Bacterial Consortia as Bioinoculants: Enhancing Soil Fertility and Crop Productivity through Synergistic Plant Growth-Promoting Mechanisms (International Journal of Scientific Research in Science and Technology, 2026)
The increasing reliance on chemical fertilisers has raised serious environmental and economic concerns, underscoring the need for sustainable alternatives in agriculture. Bacterial consortia-based bioinoculants represent a promising, eco-friendly strategy to enhance soil fertility and crop productivity. In this study, agriculturally beneficial bacteria were isolated from soil and screened for key plant growth-promoting traits, including mineral solubilization (phosphorus, potassium, and zinc), siderophore production, indole-3-acetic acid (IAA) production, extracellular enzymatic activity, and antimicrobial potential. Four efficient bacterial isolates were identified through 16S rRNA gene sequencing and were closely related to Bacillus subtilis, Pseudomonas fluorescens, and Azospirillum brasilense. Compatible isolates were combined to formulate a bacterial consortium and evaluated under pot conditions. The consortium significantly enhanced plant growth parameters, including shoot length, root length, and biomass, compared to uninoculated controls and individual isolates. The results demonstrate that bacterial consortia exhibit synergistic effects that improve nutrient availability, promote plant growth, and suppress potential pathogens. This study highlights the potential of bacterial consortium-based bioinoculants as sustainable alternatives to chemical fertilizers for improving soil health and crop productivity.